A study on students’ motivation in learning english at a primary school in Hanoi = Nghiên cứu về động lực học tiếng Anh của học sinh ở một trường tiểu học tại Hà Nội - Nguyễn, Thị Thu Hương (2020)
This research aims at finding the typically motivational pattern as well as factors that have influences on the 4th graders’ motivation in learning English at Thang Long Kidsmart Primary School from both students and teachers’ perspectives. In this study, questionnaires and semi-structured interviews were used as the main data collection instruments with the participation of sixty-five 4th graders and two Vietnamese teachers. The findings from questionnaires and interviews illustrated that the 4th graders at Thang Long Kidsmart Primary School shown their tendency towards intrinsic motivation in learning English. Additionally, the researcher found out that both teachers and students agreed factors connecting with the teachers, the learners and the parents were the three most critical elements which influence students’ motivation in English learning. However, the important degree of these factors was perceived differently by students and teachers. Other factors like the course, the group and the environment also affect the participants’ impetus for English studying to some extent. Moreover, some implications of teaching English to young learners are also recommended. At last, the result of the study is hoped to benefit teachers, students as well as parents in learning and teaching English. To motivate children to learn English, all the related parties should take active roles rather than the teachers or the learners themselves.